Reverse Engineering of a Ribosome Profiling Workflow - Silke Machauer (2015)
Ribosome profiling is a relatively new method that was only developed in 2009, but it has already enabled researches all over the world to obtain remarkable findings. By isolating the ribosome protected fragments and converting them into a cDNA library, the position on the mRNA of all ribosomes that were engaged in the process of translation at the time of cell lysis can be determined with the help of a high throughput sequencing technique. Because the method is still not well established and not yet very prevalent, the aim of this work was to reverse engineer the workflow, examining every single step closely and introducing an optimised ribosome profiling protocol for our laboratory with the future prospects of developing it further into a protocol for selective ribosome profiling that will hopefully help understanding the role of protein disulfide isomerases in co-translational folding processes.